Microanatomical insight into Reticuloepithelial cells in the Thymus of TANUVAS Aseel Chicken - Sivakumar, S.A; Kannan, T. A; Sabiha Hayath Basha; Leela, V; Vairamuthu, S; Ushakumari, S (The Indian Veterinary Journal, 2025)
This study comprehensively analyzes the histological structure of reticuloepithelial cells (RECs) in the thymus of TANUVAS Aseel birds. RECs were observed in both cortex and medulla, with a higher concentration in the medullary region. Various groups of RECs formed reticular structures in diverse shapes. The study identified three types of RECs: Type I, Type II, and Type III. Type-I RECs were noticed in the cortex, Type-II RECs were observed in both cortex and medulla and Type-III RECs were noticed at the cortico-medullary junction and in medulla. These cells play a significant role in the formation of Hassall’s corpuscles within the thymic parenchyma. The medullary regions exhibited an increased number of reticular cells around Hassall’s corpuscles compared to the cortical regions.